Storage of surinam cherry powder - Alexandre, Hofsky Vieira; de figueirêdo, Rossana Maria Feitosa; Queiroz, Alexandre José de Melo; Oliveira, Emanuel Neto Alves de (Comunicata Scientiae, 2014)
The type of drying and packaging are two essential factors in the study of dehydration andpreservation of fruits, respectively. The objective was study the storage of surinam cherry powderproduced by foam mat drying and packaged in flexible packing (PET/PP). The powder sampleswere obtained by pulp dehydration in an oven with circulating air (0.5 m s-1) in the temperature of70 °C. The surinam cherry powder was wrapped in flexible packing and stored at room temperatureand relative humidity for 60 days. During the storage was evaluated the stability of powder throughthe monitoring every 10 days the moisture content, ascorbic acid, pH, titratable acidity, reducingsugars, non reducing sugars, total sugars and color parameters (brightness, redness and yellowness).Only the non-reducing sugars did not differ significantly with the storage time. The results indicatedthat the powder has changed in most of the properties, but the ascorbic acid content, moisturecontent, total acidity and total sugars varied little over the 60 days